PENYIMPANGAN SEKSUAL DALAM HUBUNGAN SUAMI ISTRI PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG KEKERASAN DALAM RUMAH TANGGA (KDRT) - Mawardi, Mawardi (UIN Fatmawati Sukarno Bengkulu, 2017)
This research raises the problem about sexual deviation in the relationship of husband and wife of Islamic law perspective and Law No. 23 of 2004 on Domestic Violence. Based on the analysis can be disipmulkan that form of sexual deviation husband to wife like: (1) sexual sadism which is one form of variation in relationship of husband and wife. The behavior of sexual sadism involves giving a stimulus to her partner in a sadistic way. This behavior is usually accompanied by the act of tying his partner, close his partner’s eyes, and silenced his partner’s mouth. (2) Fucking at the wife’s rectum because it can be likened to liwath (homo sex), because the rectum is a dangerous and dirty place. Analysis of Islamic law against sexual deviation (sexual sadism) also contains elements of persecution and danger. Which element of persecution and danger is prohibited by Islam. Because it can harm yourself and others, and not in accordance with the goals of Islam that brings grace to the universe that requires all human beings to live in a state of serenity and at the same time eliminate the danger to mankind. While in some verses, the Qur’an has hinted that Allah Almighty. Do not like people who like to do damage and persecution (kemafsadatan). Sexual lapses of husbands against wives according to Article 8 Letter A of Law no. 23 of 2004 includes violent acts defined as any act of coercion of sexual intercourse, coercion of sexual intercourse in an unnatural way and or disliked by a wife.